Pain Levels after Local Anaesthetic with or without Hyaluronidase in Carpal Tunnel Release: A Randomised Controlled Trial - G. Yeo; A. Gupta; G. Ding; H. Skerman; M. Khatun; D. Melsom (Advances in Orthopedics)
Purpose. Hyaluronidase is an enzyme that temporarily liquefies the interstitial barrier, allowing easy dispersal of local anaesthetic through cleavage of tissue planes. This prospective, blinded, randomised controlled study investigates the utility of adding hyaluronidase to local anaesthetic in the setting of carpal tunnel release. Methods. 70 consecutive carpal tunnel release patients were recruited and randomised into a control group only receiving local anaesthetic and a hyaluronidase group receiving both hyaluronidase and local anaesthetic. Pain scores were rated using the visual analogue scale (VAS) by patients immediately after local anaesthetic injection and again immediately after the carpal tunnel release. Results. Preoperative VAS scores, taken after local anaesthetic injection, were greater than postoperative VAS scores. Postoperative VAS scores were significantly lower in the hyaluronidase group and tourniquet times were significantly shorter in the hyaluronidase group. Conclusion. Hyaluronidase addition to local anaesthetic in carpal tunnel release resulted in significant reductions in operative time and pain immediately after operation.